PEMBERDAYAAN PEREMPUAN DALAM MENGATUR KESEHATAN DAN PENINGKATAN PEREKONOMIAN KELUARGA [WOMEN EMPOWERMENT IN HEALTH REGULATIONS AND IMPROVED FAMILY ECONOMY] - Latifa Siswati; M. Rizal; Ambar Tri Ratna Ningsih; Riski Novera Y. (Jurnal Sinergitas PKM & CSR, 2017)
Women are the mobilizer in managing health and improving family economy. Women's participation in the economic field is one indicator of increasing welfare. When women have independent income, this is a sign of increased household welfare. It needs to empower women to manage family health and income. The purpose of dedication is 1) the empowerment of women in managing the health and family economy, 2) describe the results of women's empowerment in managing family health and family economy. The activity was held in Bukit Agung Village, Kerinci Kanan District, Siak Regency, Riau Province. The method used is survey and interview method. The technique of selecting the participants is done by purposive sampling that is the farmer who received the fish assistance from Indosawit Subur company. The results of this activity showed that after training there was an increase of knowledge about the benefits of consuming fish (80%), processing fish into nuggets and fish meatballs (80%), nugget and fishballs (80%), and fish (60%) . After being trained, participants have used fish not only fried, grilled and burned but have been able to make fish nuggets and fish meatballs for family consumption.Keywords: empowerment, women, health, economy.